2016
DOI: 10.18632/oncotarget.9897
|View full text |Cite
|
Sign up to set email alerts
|

WHSC1L1 drives cell cycle progression through transcriptional regulation of CDC6 and CDK2 in squamous cell carcinoma of the head and neck

Abstract: Wolf-Hisrchhorn Syndrome Candidate 1-Like 1 (WHSC1L1) is a protein lysine methyltransferase that is recurrently amplified (8p11.23) in patients with squamous cell carcinoma of the head and neck (SCCHN). In this study, we investigated the oncogenic role of WHSC1L1 in SCCHN. Using immunohistochemistry on tissue microarrays of patients with locoregionally advanced SCCHN, we found that WHSC1L1 is significantly overexpressed in patients with SCCHN, and is associated with poor grade and heavy smoking history. Knockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 26 publications
(36 reference statements)
2
32
1
1
Order By: Relevance
“…Given the absence of correlations with survival and the fact that EGFRK721me1 levels increased significantly in the transition from normal squamous epithelium to dysplasia and SCCHN, EGFRK721me1 may be important in the initial stage of head and neck oncogenesis. This finding is in accordance with our previous report for WHSC1L129.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Given the absence of correlations with survival and the fact that EGFRK721me1 levels increased significantly in the transition from normal squamous epithelium to dysplasia and SCCHN, EGFRK721me1 may be important in the initial stage of head and neck oncogenesis. This finding is in accordance with our previous report for WHSC1L129.…”
Section: Resultssupporting
confidence: 94%
“…We previously reported that WHSC1L1 is significantly overexpressed in SCCHN samples compared to normal epithelium29. To assess the pattern and levels of EGFRK721me1 in SCCHN, we performed immunohistochemical staining of 127 SCCHN samples, 21 normal squamous and 18 dysplastic epithelial samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This encodes a novel methyltransferase recently found to promote monomethylation of histones and signal activation of membrane and nuclear epidermal growth factor receptor (EGFR) (Saloura et al, 2016, 2017). Chr 11q gene KDM2A is a histone demethylase implicated in the activation of genes involved in stemness, differentiation, and inflammation (Chen et al, 2017).…”
Section: Resultsmentioning
confidence: 99%